Pembentukan Gas Metan dari Karbon Dioksida Menggunakan Katalis Ni/Al2O3 dengan Penambahan Mn Sebagai Promotor - Jihan Syahira Syifa Friema; Robert Junaidi; Mustain Zamhari (Fakultas Teknik, 2023)
Carbon dioxide (CO2) emissions are a type of greenhouse gas emission which is the main factor in the emergence of the global warming phenomenon. Based on the total CO2 emissions released, there are 3 components that most influence high CO2 emissions, namely the electricity sector (42%), transportation (23%) and housing (6%). The trend of increasing CO2 will continue if no preventive measures are taken globally. One of these preventive efforts is to convert carbon dioxide (CO2) into methane (CH4), or known as the methanation process of carbon dioxide. In the field of fuel, the conversion of carbon dioxide into methane gas has more advantages in terms of thermodynamics. One of the factors that determine the methanation process is the activity of the catalyst. The catalyst used in this study was the Ni/Al2O3 catalyst. Ni/Al2O3 catalyst is a catalyst that has good performance in the methane formation process. However, the Ni/Al2O3 catalyst has disadvantages, one of which is that it is susceptible to carbon deposition and sintering on the catalyst. One way to improve catalyst stability performance is by adding a promoter. This research was carried out by varying the temperature, the amount of Ni/Al2O3 catalyst and adding a promoter to give structural changes to the catalyst. The results showed that the temperature and the amount of catalyst affect the amount of CH4 formed, and the addition of manganese (Mn) initiator can affect the pore structure of the catalyst.